(untitled) (Eurasian Scientific Herald, 2022)
This paper attempts to provide a linguistic description of the discourse. The aim of the study is a theoretical description of discourse in linguistics, the current provisions of linguistics in relation to discourse. It also defines the concept of discourse in linguistics, clarification of its nature and relation to the related category of "text"; discourse is analyzed as a wide research field in the system of modern scientific knowledge; critical analysis of the philosophical, methodological, psychological and sociological foundations of discourse analysis; description of categories, approaches and organization of discourse.